EXPERIMENTAL STUDY THE EFFECT ANGLE OF BLADE ON THE ELECTRICAL POWER OUTPUT OF PROPELLER PICOHYDRO TURBINE - Abdullah Shalih; Purwadi Joko Widodo; Dwi Aries Himawanto (Universitas Sebelas Maret, 2019)
This study aimed to analyze the effect of angle of blade on the horizontal flow to the performance of the propeller water turbine. The experiments were performed using several test parameters including the angle of blade on the variation mass flow rate of water. With potential head 2 meters and variated turbine blade angle to achieved optimal power generated. The result showed that the variation of angle of blade with 300 angles and 11.6 l/s mass flow rate of water was the best variation to improve the performance of the propeller water turbine. The best variation can generated 32 Watt of electric power.